2014
DOI: 10.1007/s00128-014-1368-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Elimination of Brazilian Entomopathogenic Bacillus by Non-target Aquatic Species: An Experimental Study

Abstract: Ecotoxicity tests are key to predict environmental hazards resulting from chemical and biological pesticides in non-target species. In order to assess the effects of microbial pesticides it is important to determine if they cause infection in test organisms. At present the microbial elimination rate or clearance is not included in ecotoxicological regulatory protocols. This study evaluated the elimination of Bacillus thuringiensis and Bacillus sphaericus from fish and snails, after 30 days' exposure to commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This author showed that spores were rarely detected in fish after 8 days (192 h). In a similar study [ 28 ], it was demonstrated that the Brazilian fish Hyphessobrycon eques and snail B. glabrata eliminated the spores of B. thuringiensis and B. sphaericus tested strains from their body after 7 days of recovery in clean water. In snails, it was observed that CFUs of B. sphaericus were found in higher numbers after 68 h of recovery, but in any case, the tendency presented by the obtained data shows that total elimination is imminent and that the persistence of spores or the bacteria for a time does not seem to be deleterious to the organism.…”
Section: Microbial Pesticidesmentioning
confidence: 95%
See 1 more Smart Citation
“…This author showed that spores were rarely detected in fish after 8 days (192 h). In a similar study [ 28 ], it was demonstrated that the Brazilian fish Hyphessobrycon eques and snail B. glabrata eliminated the spores of B. thuringiensis and B. sphaericus tested strains from their body after 7 days of recovery in clean water. In snails, it was observed that CFUs of B. sphaericus were found in higher numbers after 68 h of recovery, but in any case, the tendency presented by the obtained data shows that total elimination is imminent and that the persistence of spores or the bacteria for a time does not seem to be deleterious to the organism.…”
Section: Microbial Pesticidesmentioning
confidence: 95%
“…In another publication, B. thuringiensis and B. sphaericus in concentrations of 10 6 spores/mL were not lethal to the fish Hyphessobrycon eques , also called Mato Grosso fish, in Brazil [ 28 ].…”
Section: Microbial Pesticidesmentioning
confidence: 99%
“…israelensis ( Bti ) on fathead minnows, Pimephales promelasandas , or fish mortality. Moreover, upon the transfer to Bt -free water, fishes effectively excreted the toxins from their organisms [ 157 , 158 ]. No genotoxic or mutagenic effects of Bt toxins on peripheral erythrocyte cells of Oreochromis niloticus were observed [ 154 ].…”
Section: Vertebratesmentioning
confidence: 99%